2020
DOI: 10.18632/aging.102708
|View full text |Cite
|
Sign up to set email alerts
|

Araloside C attenuates atherosclerosis by modulating macrophage polarization via Sirt1-mediated autophagy

Abstract: Atherosclerosis-related cardiovascular disease is still the predominant cause of death worldwide. Araloside C (AsC), a natural saponin, exerts extensive anti-inflammatory properties. In this study, we explored the protective effects and mechanism of AsC on macrophage polarization in atherosclerosis in vivo and in vitro. Using a high-fat diet (HFD)-fed ApoE-/-mouse model and RAW264.7 macrophages exposed to ox-LDL, AsC was evaluated for its effects on polarization and autophagy. AsC significantly reduced the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…As shown in Figure 1B , treatment with CK less than 2.5 μg/ml did not influence cell viability. Based on the previous study ( Luo et al, 2020 ), we used 80 µg/ml ox-LDL to induce the formation of foam cells in this study. According to oil red O results ( Figures 1C, D ), lipid accumulation was increased by ox-LDL, whereas it was decreased in the group treated with CK at different concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 1B , treatment with CK less than 2.5 μg/ml did not influence cell viability. Based on the previous study ( Luo et al, 2020 ), we used 80 µg/ml ox-LDL to induce the formation of foam cells in this study. According to oil red O results ( Figures 1C, D ), lipid accumulation was increased by ox-LDL, whereas it was decreased in the group treated with CK at different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Moderate autophagy can inhibit the formation and development of atherosclerotic plaques. Our previous studies have demonstrated that macrophage autophagy can reduce the formation of foam cells and the secretion of inflammatory factors and promote the transformation of macrophages to the M2 phenotype (Luo et al, 2020). In addition, the genetic knockout of the key autophagy gene Atg5 can significantly inhibit cholesterol leakage and promote the formation of foam cells (Singh et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations